2007
DOI: 10.1192/bjp.bp.106.025684
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, post-traumatic stress disorder and depression in Korean War veterans 50 years after the war

Abstract: Effective intervention is necessary to reduce the considerable psychological morbidity experienced by Korean War veterans. Attention to risk factors and early intervention will be necessary to prevent similar long-term psychological morbidity in veterans of more recent conflicts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 34 publications
4
36
0
3
Order By: Relevance
“…The results of this study support previous research showing both short-term and long-term effects of war (Chatterjee et al, 2009;Hunt & Robbins, 2001a;Ikin et al, 2007;Seal et al, 2007;Solomon et al, 2009;West & Weeks, 2006). The interviewees' PTSD was not measured but they expressed many feelings and thoughts that can be understood as stress and anxiety.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this study support previous research showing both short-term and long-term effects of war (Chatterjee et al, 2009;Hunt & Robbins, 2001a;Ikin et al, 2007;Seal et al, 2007;Solomon et al, 2009;West & Weeks, 2006). The interviewees' PTSD was not measured but they expressed many feelings and thoughts that can be understood as stress and anxiety.…”
Section: Discussionsupporting
confidence: 88%
“…They called for a lifespan perspective in order to study the long-term consequences and effects of military service and wartime experiences on ageing. Studies conducted 20 years postconflict (Solomon, Helvitz, & Zerach, 2009) and 50 years post-conflict (Hunt & Robbins, 2001a;Ikin et al, 2007) have shown that war veterans suffer from PTSD for decades after war. Schnurr, Spiro, Vielhauer, Findler, and Hamblen (2002) concluded that trauma was highly prevalent among veterans from World War II and the Korean conflict but that few of them experienced lifetime PTSD.…”
Section: Introductionmentioning
confidence: 98%
“…Part of a larger investigation that found substantial psychological morbidity in these veterans,16 this study explores several domains of quality of life and well-being including satisfaction with life as a whole, perception of general physical and psychological health status, social relationships and the adequacy of environment. Aspects of Australian Korean War service, including age and rank at deployment, being wounded in action and severity of combat exposure are investigated for their association with quality of life 50 years after the war.…”
mentioning
confidence: 99%
“…12 The 6122 represented 81.4% of the entire surviving repatriated group so that 19% appears to be a very low figure in the present hospitalized sample. It must be remembered, however, that a number of the MR veterans had served only in Australia and the data were never considered adequate to estimate the probable prevalence of PTSD at that time.…”
Section: Discussionmentioning
confidence: 72%
“…12 Long-term follow up is clearly desirable but time is running out for veterans hospitalized during and shortly after WWII. 18 …”
Section: Discussionmentioning
confidence: 99%